Do leaders have an influence on strengthening entrepreneurial orientation? Empirical evidence from SMEs of Turkish techno-parks - Baysak, Birol; Bozkurt, Serdar; Gunsel, Ayse (EMERALD GROUP PUBLISHING LTD, 2023)
Purpose In this study, the authors aim to test the reflections of two so-called universal leadership styles -paternalistic leadership (PL) and transformational leadership (TL)- on entrepreneurial orientation (EO) and ultimately on firm performance (FP) within the context of SMEs of a developing country, Turkey. Moreover, examining the contingency of uncertainty avoidance (UA) on the relationship between EO and firm performance is another aim of the study. Design/methodology/approach In this explanatory cross-sectional study, by studying a dataset of 345 small and medium-sized (SME) Techno-park companies in Turkey based on using the Partial Least Squares (PLS) method, the authors try to examine the antecedent role of PL and TL on EO and ultimately on FP. Moreover, we followed a mediation procedure to reveal the mediator role of EO on the relationship between leadership style and firm performance. Finally, the authors also conducted a moderation analysis through SmartPLS 3.0 to explore the contingency of UA on the relationship between EO and firm performance. Findings Study results indicate that TL is a significant antecedent of EO that results in higher firm performance. However, while PL has a negative impact on entrepreneurial orientation, the results provide no statistical evidence in support of a significant relationship between PL and firm performance. Moreover, the findings indicate that the higher UA, the weaker the relationship between EO and firm performance. Practical implications Managers, following a TL approach, can successfully encourage their subordinates to be innovative and creative. Transformational leaders are conducive to both entrepreneurship and firm performance within the context of technology-based startups. Besides, avoiding the risks and uncertainties naturally weakens the consequences of EO. Hence, EO, as an essential intangible resource, requires a proper cultural context to result in a competitive advantage. Originality/value This research provides a comprehensive understanding regarding the interrelationships amongst transformational and paternalist leadership styles, EO and firm performance within an UA context in Small Business and Technology Development Centers (SBTDCs) and Techno-parks. To the best of the authors' knowledge, no other researcher has studied those links in a holistic manner in general, particularly on the SMEs of Techno-park firms of a developing Eastern country. The findings significantly enrich the literature on paternalist leadership and entrepreneurship orientation in a cultural context.
Keywords: Transformational leadership; Paternalistic leadership; Entrepreneurial orientation; Uncertainty avoidance; Firm performance; CORPORATE ENTREPRENEURSHIP; BUSINESS PERFORMANCE; MODERATING ROLE; TRANSACTIONAL LEADERSHIP; FINANCIAL PERFORMANCE; COMPETITIVE ADVANTAGE; CULTURAL INFLUENCES; Computer Science